Microstructural evolution and high-temperature strengthening mechanisms of the IN 738LC superalloy prepared by selective laser melting - Chenyu Yang; Rui Hu; Xinxin Liu; Yajun Wang; Jie Bai; Rui Ma (Journal of Materials Research and Technology, 2024)
Defect-free SLM-IN 738LC superalloy samples were fabricated using selective laser melting (SLM). The as-built samples exhibit a cellular structure with fine carbides, γ′ phases, and high-density dislocations at the cell boundary and nano-size γ′ phases in the interior, resulting in excellent deformation resistance and favorable mechanical properties at room temperature, with a yield strength (YS) of 970 MPa, an ultimate tensile strength (UTS) of 1263 MPa, and an elongation (EL) of 33%. This study investigates the evolution behavior of the γ′ phase at different solid solution treatment (SHT) temperatures and its impact on alloy strength and toughness. The 1020 + AHT sample exhibits a uniform distribution of coarse γ′ phases. The samples subjected to 1070 + AHT and 1120 + AHT display a bimodal distribution of γ′ phases. When the SHT temperature was further increased, fine spherical γ′ phases are evenly distributed in the 1160 + AHT and 1200 + AHT samples. Moreover, the γ/γ′ eutectics at the grain boundaries gradually dissolve with increasing SHT temperature, whereas the size and fraction of carbides increase. The room temperature tensile test of the 1070 + AHT sample demonstrated a favorable balance between strength and plasticity (YS = 1217 MPa, UTS = 1472 MPa, EL = 9.25%). This is attributed to the synergistic strengthening effect of the bimodal distribution of the γ′ phase. The temperature-dependent deformation behavior of the 1070 + AHT sample was analyzed at 23 °C, 800 °C, 900 °C, and 1000 °C. At 23 °C, numerous dislocations accumulated around the γ/γ′ interfaces. When the temperature increased to 800–900 °C, the dislocations shearing γ′ phases is activated and the alloy remained high strength. At 1000 °C, both the dislocation shearing and dislocation bypassing mechanisms coexist, resulting in a decrease in the strength of the alloy and an increase in its plasticity. This work provides scientific and theoretical support for SLM-IN 738LC parts with favorable properties.